Modal analysis on cnc milling cutting tool - Nik Muhamad Firdaus, Nik Salahuddin (2013)
To date, milling is one of the most common manufacturing process for manufacturing sectors, aerospace, and tool and dies industries. In this project, the main objective is to study the dynamic properties and behaviour of the CNC milling cutting tool. The method used is using finite element analysis and the validation of results obtained using experimental modal testing. Firstly, the structural threedimensional solid modelling of the selected CNC cutting tool draw before analysed using the linear modal analysis approach. After that, the experimental modal testing was performed using Modal Impact Hammer Testing method. The natural frequency of the mode shape is determined and comparative study was done from both method results. The results of this project shown the mode shape simulation of experimental data are totally not same but generally is in agreement with the finite element analysis. It is concluded that the experimental method uses vertical milling machines as test rig and the difference mass of cutting tool affected the result.